The Role of a Research Administration Program in Adverse Event Reporting - Fedor, Carol; Cola, Philip; Polites, Stephanie (The journal of research administration, 2007)
The reporting, analysis, and management of adverse events (AEs) provide an ongoing assessment of risk in the context of a clinical trial and enhance the protection of human research participants and the informed consent process. Effective and efficient review of AEs has been a long-standing challenge for Institutional Review Boards (IRBs) and Research Administration programs, especially as protocols and ethical/legal issues become more complex. Furthermore, AE reporting is governed by many different regulations and sources, with inconsistencies in standards and requirements. Reporting standards for AEs were adopted when single-center clinical trials were the norm. With the increased prevalence of multi-center trials, IRBs are now inundated with AE reports. This paper will review the current issues in AE reporting and the challenges encountered by research administration programs when reassessing current policies and procedures and implementing a significantly revised reporting policy. The implementation plan and educational strategies used with the investigators and research staff will be described. Preliminary outcome data will be presented to evaluate policy revisions and to take into consideration the concepts of "quality of review" versus "quantity of reporting." [PUBLICATION ABSTRACT]